Determination of the Impact Index of Covid19 in El Salvador through demographic, environmental and epidemiological relationship - Alvarado Batres, César Armando (2020)
This study was carried out during the Covid19 pandemic that originated in the Republic of China at the end of 2019 and has spread throughout the world since then, taking official records of demographic, environmental and epidemiological information in El Salvador , with the aim of developing a quantitative and qualitative process that demonstrates the variations in cases of Covid19 contagion as a consequence of the pandemic, based on three factors, including the environmental variable; since this can be an agent that regulates the mobility of the pandemic vectors. In addition, the importance of the use of Geographic and Satellite Information Systems is demonstrated, which allow a more complete analysis of health problems at the national, regional and / or global level; above all in decision-making on public health policies, since the lack of knowledge for decision-making in the face of this new pandemic has been evidenced. The most substantial product of this research is a thematic map of the impact of the pandemic at the country level divided by municipalities, where it shows that the cities with the highest population density and the lowest environmental quality are those that have been most affected. Therefore, in the future it is necessary not to centralize all economic activity in a few places, in addition to the importance of the environments that exist in each municipality for the well-being of people. Finally, a statistical analysis is carried out through the decision tree that supports the aforementioned.